Matlab Simulation of an Induction Generator Based Ac/Dc Hybrid Electric Power Generation System: Efficiency and Hardware Reduction in AC/DC Hybrid Electric Power Generation System for More Electric Aircraft (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In more electric aircraft (MEA) system, both AC and DC electric power with multiple voltage levels are required for various aircraft loads. This paper presents an induction generator based ACDC hybrid electric power generation system for MEA. In the proposed system architecture, a high speed induction startergenerator and a low speed induction generator are installed on the high pressure (HP) and low pressure (LP) spools of the engine, respectively. In generating mode of operation, all of the constant voltage variable frequency AC power is generated by the HP generator while the DC power demand is shared by both HP and LP generators. A control scheme is developed to regulate the AC load voltage and coordinate DC power generation between the two generators. The proposed induction generator based ACDC hybrid generation system results in reduced hardware requirement compared to both AC and DC primary generation systems.